Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1172/jci97924
|View full text |Cite
|
Sign up to set email alerts
|

DNA methyltransferase expression in triple-negative breast cancer predicts sensitivity to decitabine

Abstract: Triple-negative breast cancer (TNBC) is a heterogeneous disease with poor prognosis that lacks targeted therapies, especially in patients with chemotherapy-resistant disease. Since DNA methylation-induced silencing of tumor suppressors is common in cancer, reversal of promoter DNA hypermethylation by 5-aza-2'-deoxycytidine (decitabine), an FDA-approved DNA methyltransferase (DNMT) inhibitor, has proven effective in treating hematological neoplasms. However, its antitumor effect varies in solid tumors, stressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
111
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(121 citation statements)
references
References 86 publications
(88 reference statements)
7
111
0
Order By: Relevance
“…This antibody detected a modest increase in 89 kD PARP1 levels by 48 hr of 5-aza-dC treatment in K562 cells, and clearly increased levels in K562 cells treated with 5-aza-dC for 66 hr, and GM639 cells treated with 5-aza-dC followed by PARPi. DNMT1 levels were dramatically reduced upon 5-aza-dC treatment, as also documented in other cell types (Ghoshal et al, 2005;Yu et al, 2018). Surprisingly in K562 but not GM639 cells, DNMT1 levels began to recover at 66 hr; and treatment with PARPi alone or together with 5-aza-dC caused DNMT1 levels to increase.…”
Section: Treatment With 5-aza-dc And/or Parpi Induces Apoptotic Cleavsupporting
confidence: 69%
See 1 more Smart Citation
“…This antibody detected a modest increase in 89 kD PARP1 levels by 48 hr of 5-aza-dC treatment in K562 cells, and clearly increased levels in K562 cells treated with 5-aza-dC for 66 hr, and GM639 cells treated with 5-aza-dC followed by PARPi. DNMT1 levels were dramatically reduced upon 5-aza-dC treatment, as also documented in other cell types (Ghoshal et al, 2005;Yu et al, 2018). Surprisingly in K562 but not GM639 cells, DNMT1 levels began to recover at 66 hr; and treatment with PARPi alone or together with 5-aza-dC caused DNMT1 levels to increase.…”
Section: Treatment With 5-aza-dc And/or Parpi Induces Apoptotic Cleavsupporting
confidence: 69%
“…5-aza-dC is incorporated into DNA of replicating cells, where it may become a target for methylation by the maintenance DNA methyltransferase, DNMT1. Treatment with 5-aza-dC rapidly induces proteolysis and depletion of DNMT1, resulting in genome-wide loss of cytosine methylation and extensive epigenetic reprogramming (Ghoshal et al, 2005;Patel et al, 2010;Yu et al, 2018). The possibility that DNA demethylation might re-activate silenced tumor suppressor genes to limit cell proliferation provided the initial rationale for the use of 5-aza-dC in therapy of cancer, and 5-aza-dC is 2 commonly considered an "epigenetic" drug (Estey, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies showed that miR‐155 is upregulated in TNBC, but whether miR‐155 is involved in stemness and DCA resistance in BC has not been studied. Studies have shown that DNMT expression in TNBC is associated with sensitivity to DCA 33 . Studies have also shown that miR‐155 is a novel marker of TNBC chemoresistance 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that DNMT expression in TNBC is associated with sensitivity to DCA. 33 Studies have also shown that miR-155 is a novel marker of TNBC chemoresistance. 15 Our findings support the notion that miR-155 promotes the stem cell characteristics, the colony-forming ability, and the DCA resistance of TNBC cells.…”
Section: Discussionmentioning
confidence: 99%
“…If residual tumor remained after chemotherapy was complete, another sample of tumor tissue was collected during surgical resection for derivation of a treatment‐resistant PDX. In the PDX model, a relationship between DNA methyltransferase ( DNMT ) expression and response to decitabine was observed, where PDXs with high expression of DNMT3A and DNMT3B exhibit an enhanced response to decitabine, suggesting that decitabine may be an alternative therapy for certain individuals. Such targeted therapies, based on individual tumor somatic genotypes using pharmacogenomic approaches, will yield additional therapeutic targets in the near future to further precision oncogenic strategies.…”
Section: Integrating Pharmacogenomic Information Into Medical Practicementioning
confidence: 99%